RISK FACTORS RELATED TO CONTACT DERMATITIS IN WORKERS DUE TO PESTICIDE EXPOSURE IN PALM OIL PLANTATIONS - Maksuk, Maksuk; Ardiansyah, Ardiansyah; Kumalasari, Intan (Indonesia Epidemiological Journal, 2022)
Pesticides are the most widely used chemicals to control pests and diseases in Indonesia, especially in plantations, including oil palm plantations. Exposure to pesticides can cause health problems and death. One of the most common health problems caused by exposure to pesticides is contact dermatitis. This research was an analytic observational with a cross-sectional design. This research was conducted in oil palm plantations in Banyuasin Regency in April - October 2016, with a sample of 60 respondents; the samples were taken randomly. The results of the analysis found contact dermatitis (62%), incomplete use of personal protective equipment (58.3%), eating/drinking/smoking during application (61.7%), and not decontaminating after exposure to pesticides (76.7%). Statistical test results showed that length of work, respiratory exposure, use of personal protective equipment, and decontamination after spraying were associated with contact dermatitis (p v < 0.05). Workers cause contact dermatitis after spraying, not cleaning the body, and not using personal protection completely and according to standards. Therefore, companies must provide a special room for cleaning the body, and personal protective equipment must be available completely and according to standards.